Repressor activator protein 1–promoted colorectal cell migration is associated with the regulation of Vimentin. Issue 4 (April 2017) - Yang, Yongyong; Ye, Chunxiang; Wang, Lixin; An, Guo; Tian, Zhihua; Meng, Lin; Qu, Like; Lian, Shenyi; Shou, Chengchao
Repressor activator protein 1 plays important roles in telomere protection, while repressor activator protein 1 binds to extra-telomeric DNA and exerts the function as a transcriptional regulator. Previous study showed that repressor activator protein 1 regulates the transcriptional activity of nuclear factor-κB, and it was highly expressed in breast cancer tissues; however, the clinical significance of repressor activator protein 1 expression in cancer remains to be elucidated. In this study, we discovered that repressor activator protein 1 was highly expressed in colorectal cancer tissues. High expression of repressor activator protein 1 was significantly correlated with poor prognosis and distant metastasis. Knockdown of repressor activator protein 1 in colorectal cancer cells did not affect cell proliferation or colony formation, but dramatically decreased cell migration and F-actin-enriched membrane protrusions. Microarray screening revealed that Vimentin was downregulated after repressor activator protein 1 knockdown, which was validated by analysis of a colorectal cancer dataset. Furthermore, knockdown of Vimentin attenuated repressor activator protein 1–enhanced cell migration. Thus, our study suggests that repressor activator protein 1 is a prognostic marker and a potential target for colorectal cancer therapy.